Biaxial flexure strength and physicochemical characterization of a CAD/CAM lithium disilicate ceramic: effect of etching time, silane, and adhesive applications - Silva, Sarah Emille Gomes da; Araújo, Gabriela Monteiro de; Souza, Karina Barbosa [UNESP]; Moura, Dayanne Monielle Duarte; Aurélio, Iana Lamadrid; May, Liliana Gressler; Vila-Nova, Taciana Emília Leite; Zhang, Yu; Souza, Rodrigo Othávio de Assunção e (Springer Nature, 2022)
Objective: To evaluate the effect of different acid etching time and bonding agent (silane and/or adhesive system) on biaxial flexural strength and physico-chemical properties of a lithium disilicate ceramic. Material and methods: One hundred twenty ceramic discs were made and divided into 8 groups (n = 15) according to factors “etching time” (20 and 120 s) with hydrofluoric acid (HF) and “bonding agent” (C, no bonding agent; S, silane, A, adhesive; and SA, silane + adhesive). After surface treatment, a resin cement layer was applied to the surface and all specimens were subjected to biaxial flexural strength (BFS) test with treated surfaces loaded in tension (1 mm/min). The Weibull analyses and complementary analyses were also performed. Statistical analysis was done with 2-way ANOVA and the Tukey test (α = 0.05). Results: ANOVA revealed that the factors “etching time” (p = 0.0003) and “bonding agent” (p = 0.007) were statistically significant. In the overall analysis, the HF120S group (272.02 ± 35.30A MPa) presented significantly higher BFS than that of HF120C (218.45 ± 17.15CD MPa) and HF20S (228.40 ± 37.83BCDMPa). On the other hand, the HF20A group (208.92 ± 31.16D MPa) had significantly lower BFS than HF120S (272.02 ± 35.30A), HF120A (254.42 ± 26.87ABC) and HF120SA (259.30 ± 36.55AB) groups (Tukey). The Weibull modulus (m) of all groups was significantly different from each other (p = 0.000). Conclusions: Regardless of etching time, the application of silane alone is sufficient to increase the flexural strength of glass ceramic, eliminating the need for the application of adhesive systems. Moreover, if only silane or adhesive is applied, 120-s HF application should increase the flexural resistance of the lithium disilicate ceramic. Clinical significance. Applications of adhesive systems after silanization can be suppressed from the surface treatment protocol of glass ceramics, since it does not improve their mechanical strength.
Keywords: Dental ceramics; Flexural strength; Glass–ceramics; Surface treatment